A Comparative Study of Emotional Intelligence Between Handball Players Aged (13-15) Years - Ghazi, Abdul Wahab; Mitab, Foad (Journal of Physical Education, 2016)
The research aimed at Identify the differences of the emotional intelligence bygender variable (male / female) and for all members of al- resafa educational directorateplayers. The research hypothesesis:- There is no significant differences in emotionalintelligence by gender variable (male / female), and for all members samples of al- resafa educational directorate players. The basic procedures contains: Sample of players from alresafa educational directorate representing (80), and they (40) from each directorate . Thesample selected in intentional way. The results were processed and extracted using (SPSS).Some of the conclusions reached by the researchers as follows:- al- resafa (1) directorateeducational players have more than al- resafa (2) directorate educational players. Some ofthe recommendations were as follows: - Need to focus on collective activities, especiallysports ones, which would support the skills of emotional intelligence as well as increasinginterest in teachers colleges unrelated to sports to clarify the importance of physical activityfor players and impact on the personal.